Exploring Global Competence and Inclusive Spirituality in Professional Teacher Education - Khairunnisah Khairunnisah; Puguh Wahyu Prasetyo; Ikmi Nur Oktavianti (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This research aims to explore global competence and inclusive spirituality in teacher professional education (PPG) within the context of the digital era and diversity. This study is based on a transformative reflective learning approach that integrates the principles of deep learning and religious moderation literacy as pedagogical foundations. The research subjects consisted of 21 PPG students at Universitas Muhammadiyah Tapanuli Selatan. Data were collected through reflective journals, in-depth interviews, and classroom then analyzed thematically using Braun and Clarke's (2006) six-phase framework. Findings revealed five main themes: (1) transformation of perspectives on diversity (17/21 participants); (2) reflective learning practices that foster inclusive spirituality (14/21); (3) contextual pedagogical strategies shaping global competence (16/21); (4) structural and cultural challenges in implementing moderation values (11/21); and (5) changes in the role of prospective teachers from material conveyors to value facilitators (19/21). This study offers conceptual and practical contributions to understanding value-based PPG practices and strengthens the role of teachers as agents of change in a pluralistic society.